Efficacy of botulinum toxin in modifying spasticity to improve walking and quality of life in post-stroke lower limb spasticity - a randomized double-blind placebo controlled study - Anupam Datta Gupta; Renuka Visvanathan; Ian Cameron; Simon A. Koblar; Stuart Howell; David Wilson (BMC Neurology, 2019)
Abstract Background Post-stroke lower limb spasticity (PSLLS) has a prevalence of 28–37%. PSLLS can cause difficulty in walking and reduce quality of life (QOL). Post stroke spasticity impairs the ability to intervene to improve walking ability. Botulinum Toxin A (BT) is an effective intervention for focal spasticity, but its use is currently restricted in many countries by their reimbursement system stating that the evidence for improvement in walking and quality of life (QOL) is not robust for treatment in the lower limb. This randomized control trial (RCT) will investigate the effectiveness of BT in modifying spasticity, and improving functioning (mobility, walking, activities of daily living (ADL’s) and QOL. Methods/design A double-blind placebo-controlled trial injection will assess the effect of BT compared with a placebo (normal saline) in a sample of n = 94 patients. Following treatment of spasticity measured by Modified Ashworth Scale (MAS), the primary outcome of gait velocity will be measured by i) Gait Rite (Electronic Walkway); ii) walking by 2 Min Walk Test; iii) balance by Berg Balance Scale; mobility by iv) Timed Up and Go (TUG); v) lower limb function by ABILICO; vi) patient related goal by Goal Attainment Scale (GAS); vii) QOL by SF 12 (Rand version); viii) activities of daily living by the Functional Autonomy Measurement System (SMAF). There will be an associated health economic analysis. Discussion The study methodology is based on our systematic review 2026 studies, which concluded the evidence for improving mobility following use of BT to reduce spasticity was not robust. The results of this study could establish the use of BT in improving gait and lower limb function in PSLLS. This study could provide the evidence needed for reimbursement schemes to consider and changes to its funding policy for BT in PSLLS. Trial registration The trial is registered with the Australia New Zealand Clinical Trails Registry (ANZCTR)-ANZCTRN12617001603303. Registered 07/12/2017.